Impact of Blue Light Therapy on Wound Healing in Preclinical and Clinical Subjects: A Systematic Review: Blue Light on Wound Healing - Bayat, Mohammad; Albright, Richard; Hamblin, Michael R; Chien, Sufan (Journal of Lasers in Medical Sciences, 2022)
Introduction: While a wound caused by a minor cutaneous incision routinely heals in a short time, wounds from major surgical operations might need numerous days to heal and may leave an obvious cicatrix. The use of blue light therapy (BLT) to destroy infectious microorganisms and disrupt biofilm formation could be an efficient method for healing ulcers. This systematic review focused on the effects of BLT in different preclinical in vivo studies and clinical models of skin wound healing. Furthermore, this study attempted to determine what main light parameters should be tested in preclinical and clinical studies. Methods: The online databases PubMed.gov, Google Scholar, Scopus, Web of Science, and Cochrane were searched using the keywords “blue light” and “wound healing” according to PRISMA guidelines. No publication time limit was enforced. Results: A total of 858 articles were identified, and 17 articles in three distinct categories were included for review. They comprised two articles on humans, fourteen articles on healthy animals, and one article on diabetic animals. Conclusion: Some studies have shown that the application of BLT on preclinical and clinical models of wound healing in vivo is able to significantly accelerate the healing process. Few studies, however, have explored the bactericidal effect of BLT on skin injury repair in burn patients. Further preclinical investigations designed to provide a better understanding of the bactericidal effect of BLT using standardized protocols, different BLT wavelengths, and different stages of the wound-healing process of infected wounds and ulcers in healthy and diabetic animals should be carried out before clinical trials can be considered. BLT could eventually be a good option for treating infected chronic wounds, including those in diabetic patients.